Efficient Revocable Certificateless Encryption Secure For Wireless Body Area Networks - Shyamli, U; Ashlin Jeba, A (International Journal of Computer Sciences and Engineering, 2025)
The ageing populace worldwide is always rising, both in urban also, territorial areas. There is a need for IoT based remote wellbeing checking frameworks that take care of the wellbeing of elderly individuals without compromising their comfort also, preference of remaining at home. However, such frameworks may produce huge sums of data. The key research challenge addressed in this paper is to proficiently transmit healthcare data within the limit of the existing framework infrastructure, particularly in remote areas. In this paper, we distinguished the key framework necessities of a regular remote wellbeing checking framework in terms of constant occasion update, bandwidth necessities also, data generation. In this fast step of life, it is difficult for people to be constantly available for their near ones who might need them while they are suffering from a disease or physical disorder. So constant monitoring of the patient’s body parameters such as heartbeat level, temperature level, etc. becomes difficult. Hence to remove human error and to lessen the burden of monitoring patient’s health from doctor’s head, this project presents the methodology for monitoring patients remotely using Internet of Things. A patient monitoring system for the Internet of Things can be established through the integration of wireless body area network, communication infrastructure, and the hospital network. This project is useful in medical applications and offers less cost. The patient monitoring systems is one of the major improvements because of its advanced technology. This project describes the design of a simple, microcontroller based heart beat & temperature measuring device with IoT output. In case heart beat or pressure is abnormal condition then it will intimate us via IoT to server and mobile.